The Influence of Bureaucracy Culture to Servant Leadership, Organizational Learning and Performance of ASN Residency Service and Civil Registration in the Province of East Kalimantan - ., Sulastin; ., Brahmasari; Ratih, Brahma (Archives of Business Research, 2019)
The Ministry is the main task of a substantial apparatus, as a man of the State and of society. This task has been clearly outlined in the Preamble 1945 alenia fourth, which included four aspects of service to the Community apparatus subject matter, namely protecting Nations Indonesia and all the spilled blood of Indonesia, promote the general welfare, the intellectual life of the nation and implementing a world order based on freedom, lasting peace and social justice. Government officials are acting as the administrator of the public solely working for the benefit of the public, the public administration has the role of special obligations, namely the public role and responsibilities of the public (served on the public interest or as Royal Society). This research aims to examine and analyze the influence of the culture of the bureaucracy, to servant leadership, organizational learning and performance of ASN Department of civil registration and Residency of East Kalimantan province. The population in the study totaled 623 Echelon IV officials and employees of the Department of population and implementing civil registry of East Kalimantan province which includes 10 cities/counties and the number of samples as much as 244. Technique of data analysis using SEM with SPSS and AMOS 23 18. The research was carried out using the method of case studies where data retrieved through the dissemination of the questionnaire. Techniques in sampling is purposive sampling is a technique of determining the sample with a particular consideration and data collection methods used in this study is a questionnaire, interviews and studies library. The results of this research it can be concluded that Bureaucratic culture effect significantly to servant leadership, Bureaucratic culture effect significantly to organizational learning, Bureaucratic culture effect significantly to performance of ASN, Servant leadership does not effect significantly to Organizational learning, Servant leadership effect significantly to performance of ASN and organization learning effect significantly to performance of ASN.